PERANAN INTERNET SEBAGAI MEDIA KOMUNIKASI - Effendi, Mukhtar (Fakultas Dakwah IAIN Purwokerto, 2009)
Currently, the Internet not only become an alternative communication media, but even helped form a newcommunication patterns. Nevertheless, there has been no communication science theories that can accommodatecommunication through this internet. Meanwhile, theories of communication that already exist that can be used for runwayapproach to Internet research is the theory of the uses and gratifications which focuses on media, passive and activecommunicants. Meanwhile, supporters of reference is still a concept rather than a middle-range theory. This paper seeks toexplore existing concepts in communication via the Internet based on theories that have existed from the science ofcommunication